The Moderating Effect of Sustainability Commitment and ESG Disclosure on Corporate Credit Risk: An Analysis of the Banking Industry in Southeast Asia - Achmad Jaelani; Atik Budi Paryanti (Dinasti International Journal of Education Management and Social Science, 2026)
This research seeks to examine how the Environmental, Social, and Governance (ESG) Disclosure of debtor firms influences Credit Risk, proxied by the Non-Performing Loan (NPL) ratio, within the Southeast Asian banking sector, as well as to evaluate the moderating function of Bank Sustainability Commitment. Grounded in Signaling Theory and Stakeholder Theory, this quantitative study employs panel data from Southeast Asian listed banks covering the years 2015-2023. The regression analysis on the panel data indicates that debtor firms’ ESG Disclosure exerts a significant positive effect on bank Credit Risk (H1 supported), suggesting that strong ESG transparency signals high management quality, thereby reducing information asymmetry and the likelihood of default. A major finding also shows that Bank Sustainability Commitment significantly and positively moderates this relationship (H2 supported), amplifying the risk-reducing impact of ESG Disclosure. This implies that banks with stronger sustainability integration are more capable of leveraging ESG information for more accurate risk evaluation and mitigation. Theoretically, the study contributes to a deeper understanding of the ESG credit risk pathway by highlighting the importance of the information receiver. From a managerial standpoint, the results recommend that banks strengthen their internal sustainability commitment as a strategic approach to enhance credit risk assessment precision and optimize loan portfolio management.